Critical Leadership to Overcome Organizational Inertia and Drive Innovation in High-Performance Organizations - Jaya Roza Azzukhrufi; Fitriana Fitriana; Nunuk Hariyati; Syunu Trihantoyo; Muhammad Ahyat (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2026)
This study aims to explore leadership strategies to address the paradox of success in high-performing educational institutions, where past achievements often create strategic and cognitive inertia that hinders future adaptation. Using a Systematic Literature Review (SLR) methodology, 48 recent articles (2021–2025) from reputable databases such as Scopus and Google Scholar were synthesized. The analysis reveals that inertia in high-performing organizations manifests as an invisible cage and status quo bias, preventing innovation and adaptation. The study identifies Critical Leadership as a key mechanism to overcome this inertia through executive curiosity, digital emancipation, and interim leadership. Furthermore, Maintenance Innovation is conceptualized as a dynamic capability carried out by agile teams, enabling organizations to adapt and innovate continuously. The contribution of this study lies in its systematic synthesis of research on critical leadership, organizational inertia, and maintenance innovation in educational settings, providing a unified framework for overcoming challenges in high-performing schools. The novelty of this research lies in redefining Maintenance Innovation as a dynamic process that sustains performance amid technological disruptions, in contrast to traditional views of innovation as routine. Additionally, the study introduces Critical Leadership as a transformative, disruptive force that shifts leadership roles from merely maintaining quality to fostering productive dissatisfaction to stimulate innovation. This research offers valuable insights for educational leaders and policymakers on how to manage change and innovation while maintaining quality. However, further empirical research using quantitative and mixed-methods approaches is needed to validate these findings and assess their application across diverse educational contexts.